Acute toxicological effects of zinc oxide nanoparticles in mice after intratracheal instillation. (2nd January 2017) - Wang, Dejun; Li, Haibo; Liu, Zihong; Zhou, Jingyang; Zhang, Tianliang
Abstract: Background : Zinc oxide nanoparticles (ZnO NPs) are increasingly being used in industry. Objective: To evaluate the acute toxicology of ZnO NPs in Mice. Methods : ZnO NPs were intratracheally instilled into mice at different dose (200, 400, 800 μg/kg), which was 1, 2, or 4 times of accumulative intake in one week according to the threshold limit value. Acute toxicity was assessed by animal mortality, organ/body weight ratios, hematology, blood biochemistry, and histopathology as well as by the determination of cells, proteins, and lactate dehydrogenase activity in bronchoalveolar lavage fluid. Results : Exposure to ZnO NPs also resulted in bodyweight loss and a higher level of total cell number, total protein, and hydroxyproline content in BALF. Nitric oxide and malondialdehyde levels in the lung homogenates were also increased. In addition, inflammatory and hyperplastic changes in the lungs were observed. Conclusion: Threshold limit value (5 mg/m 3 ) may unfit for ZnO NPs.